Student Perceptions of the Infrastructure Impact on their Learning Experience - Shahi, Lok Bahadur (Karnali Outlook: Knowledge Across Disciplines, 2026)
This study attempts to explore the significance of campus infrastructures and the impact of them to the students’ learning activities. The governments and societies around the world are continuously trying to improve their education systems and ensure that all students have the opportunity to go to campus and acquire the knowledge and skills they need to lead a healthy and productive life. The key inputs to the education system, such as curricula, teachers, and infrastructures help to improve the quality of education. The goals of sustainable development are defined by the United Nations and the scope of the development agenda for all countries in the world requires countries to build and upgrade education facilities that are child, disability, and gender sensitivity, and provide the safe, non-violent, inclusive and effective learning environments for all. This studies have shown that the students’ performance has been enhanced in schools with better physical learning environments. The New technologies and emerging pedagogical practices create better spaces for students to increase the efficiency of investments in educational infrastructure. In this context, this study adopted a quantitative research design including a questionnaire using Likert scale in descriptive statistics. This study showed that the incomplete administrative and academic buildings have created the problems in students’ teaching-learning activities at the constituent campus under Mid-West University, Bheri Gyanodaya Multiple Campus, Jajarkot.